1996
DOI: 10.1002/pssb.2221980121
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Insulator Transition in Degenerately Doped Si and Ge under High Uniaxial Pressure

Abstract: Strain-induced metal-insulator (MI) transitions have been observed in degenerately doped Si:Sb and Ge:Sb crystals at T = 4.2 K and for extremely high uniaxial pressures up to 5 GPa. It is shown that in both Si and Ge the transition from a metallic-type to an activated conductivity is determined by strain-induced changes of the conduction band parameters. The data obtained demonstrate that the effective mass donor approach and the scaling theory of localization describe well the MI transition phenomenona observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In barely metallic crystals, the N c change leads to the transition to activation-type conductivity at low temperature and high magnetic field [1,2]. In this case, for n-Si at orientation of the deformation axis along [111] direction and for n-Ge at X || [100] a remarkable increase of the electron effective mass is observed that leads to a transition from metallic to activation type conductivity in the region of concentrations which essentially exceed the critical concentration N c [4,5]. The parameters of the conduction band do not change under the influence of such a type of deformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In barely metallic crystals, the N c change leads to the transition to activation-type conductivity at low temperature and high magnetic field [1,2]. In this case, for n-Si at orientation of the deformation axis along [111] direction and for n-Ge at X || [100] a remarkable increase of the electron effective mass is observed that leads to a transition from metallic to activation type conductivity in the region of concentrations which essentially exceed the critical concentration N c [4,5]. The parameters of the conduction band do not change under the influence of such a type of deformation.…”
mentioning
confidence: 99%
“…Thus, an increase of electron effective mass which occurs for both n-Si and n-Ge crystals because of C-band transformation [4] is the principle of strain-induced MIT [4,5]. Thus, an increase of electron effective mass which occurs for both n-Si and n-Ge crystals because of C-band transformation [4] is the principle of strain-induced MIT [4,5].…”
mentioning
confidence: 99%
“…The possibility of an insignificant change of the critical concentration of the MI transition in the same crystal was realized in [3] using the effect of admixing of the excited states to the ground state by applying the uniaxial stress [4] which removes the many-valley degeneracy in slightly insulating n-Si(P). The change of the critical concentration of the MI transition in more wide range was achieved in degenerately doped n-Si(P) and n-Ge(Sb) due to achieving a remarkably strain-induced increase of the electron effective mass [5].…”
Section: Introductionmentioning
confidence: 99%
“…In that case, electron delocalization was caused by an increase in the overlap of the donor wavefunctions due to a reduction of the valley±orbit splitting from a uniaxial deformation at a random orientation. The metal to insulator (MI) transition was obtained at high uniaxial stresses in degenerated crystals Si(Sb) and Ge(Sb) at a relatively high temperature T = 4.2 K [2], as compared to temperatures (T % 0), which are normally used to study this effect [3 to 5]. In degenerated crystals of n-Si and n-Ge subject to a high uniaxial deformation, the MI transition is connected with a drastic modification of the conduction band of the crystals which leads to a substantial increase in the effective mass of the electrons [2].…”
Section: Introductionmentioning
confidence: 99%
“…The metal to insulator (MI) transition was obtained at high uniaxial stresses in degenerated crystals Si(Sb) and Ge(Sb) at a relatively high temperature T = 4.2 K [2], as compared to temperatures (T % 0), which are normally used to study this effect [3 to 5]. In degenerated crystals of n-Si and n-Ge subject to a high uniaxial deformation, the MI transition is connected with a drastic modification of the conduction band of the crystals which leads to a substantial increase in the effective mass of the electrons [2]. A large decrease in the Bohr radius of the electron on an impurity center (a B h 2 came 2 ) as a result of increase in uniaxial stress X results in the localization of electrons at the impurity center and, thus, in a large increase of electrical resistivity in the region of the MI transition.…”
Section: Introductionmentioning
confidence: 99%